Advances With Non-coding RNAs in Neuropathic Pain - Hu, Cheng; He, Menglin; Xu, Qian; Tian, Weiqian (Frontiers in Neuroscience, 2021)
Abstract Neuropathic pain (NP) is one of the most common types of clinical pain. The common causes of this syndrome include injury to the central or peripheral nervous system and pathological changes. NP is characterized by spontaneous pain, hyperalgesia, abnormal pain and paresthesia. Because of its diverse etiology, the pathogenesis of NP has not been fully elucidated and has become one of the most challenging problems in clinical medicine. This kind of pain is extremely resistant to conventional treatment and is accompanied by serious complications. Noncoding RNAs (ncRNAs), such as microRNAs (miRNAs), long noncoding RNAs (lncRNAs), and Circular RNAs (circRNAs) contribute to diverse biological processes by regulating the expression of various mRNAs involved in pain-related pathways, at post-transcriptional level. Abnormal regulation of ncRNAs is closely related to the occurrence and development of NP. In this review, we summarize the current state of understanding of the roles of different ncRNAs in the development of NP. Understanding these mechanisms can help develop novel therapeutic strategies to prevent or treat chronic pain.